Dziesięcina w ustawodawstwie polskich synodów diecezjalnych w XIII -XV wieku - Zarosa, Wojciech (Saeculum Christianum. Pismo Historyczne, 2016)
The issue of tithes was a very important aspect of the diocesan synods’ legislative activity. It is also argued that tithes had a great importance for ecclesiastical institutions’ functioning. The author makes an attempt of interpretation and analysis of the most important tithe statutes which were issued between XIIth and XVth century. The author focuses on the archdiocese of Gniezno, diocese of Cracovia, diocese of Breslau, diocese of Plock and diocese of Poznan. These dioceses were responsible for customizing the canon law’s norms to regional principle. Those were issued by legate and provincial synods. It is worth noting that diocesan synods reacted for new occurrences and processes having political, economic or social character. The regulation of the internal church’s web of tithes was one of the most important issues with which the diocesan synods’ legislation had to deal with. Creation of new structures resulted in the progressive erosion of parish structures. By that time it was hard to decide who should to receive the tithes. Diocesan synods, basing on the common norms, decided to give the tithe only to those clergyman, who provided priestly activity (cura animarum). It was also banned to receive decima vagas – unspecified tithes. XVth century brought new trends of tithe payment. The nobility’s movement started to struggle with the priesthood with power and position in the Poland, which the best example and symbol was cracovian bishop – Zbigniew Oleśnicki (1423-1455). This movement stood against tithes as well and mading attempts of restraining the tithe obligations. The issue of tithes was a very important aspect of the diocesan synods’ legislative activity. It is also argument that tithes had a great importance for ecclesiastical institutions’ functioning.